Synthesis And Performance Ordered Sno2 Using Sba-16 For Detection Of Dangerous Gases - Sahrani, Muhamad Ikhwan Mohd (Universiti Sains Malaysia, 2022)
Tin oxide (SnO2) based sensor have attracted a lot of interest in the field of dangerous gas detection due to its sensitivity, fast response, and long-term stability. However, more study is still needed to improve the sensitivity and performance of SnO2 based sensors. This study focuses on the synthesis and performance of nanocasted ordered mesoporous SnO2 using the SBA-16 for the detection of harmful gases like hydrogen gas, H2. Synthesis of the SBA-16 was carried out using pluronic F-127, hydrochloric acid (HCl) and tetraethylortosilicate (TEOS), followed by hydrothermal aging treatment at temperature 80°C. The produced ordered mesoporous SnO2 was compared using two different types of infiltration namely, Conventional Evaporation Method (CEM) and Solid-Liquid Method (SLM). According to the structural characteristics discovered using XRD, BET, and SEM analysis, the Conventional Evaporation Method (CEM) demonstrates much better structure compared to Solid-Liquid Method (SLM). Following that, MATLAB was used to simulate the performance of the sensor in detecting dangerous gas, based on the obtained ordered mesoporous SnO2's physical characteristics. The experimental result indicates that the variations of the sensor sensitivity against the gas concentration, which is shown as a well-resolved curve as concentration increases the sensitivity increases until it reach the saturation level. A bell-shaped curve that similar with the experimental data from the previous research was obtained when comparing the operating temperature against the sensitivity of the sensor with variable concentration. In conclusion, sensitivity analyses depending on pore size (r) and film thickness (L) were carried out and it comes into a result where the pore size (r) has directly relationship with gas sensor sensitivity and vice versa for film thickness (L).